Critical-descriptive integration of multiple intelligences theory in the development of islamic learning methodology in the digital era - Abdurrahman; Endin Mujahidin; Santi Lisnawati (At Turots: Jurnal Pendidikan Islam, 2025)
The digital era has fundamentally changed the educational landscape, demanding innovation in learning methodologies, including in the context of Islamic education. Howard Gardner's Multiple Intelligences (MI) theory offers a rich framework for understanding the diversity of learners' potential. This article presents a critical-descriptive integration of MI theory in the development of Islamic learning methodology in the digital era. The descriptive approach is used to outline the potential of MI in designing adaptive and inclusive Islamic learning, while the critical approach highlights the challenges and limitations that may arise. This integration has the potential to create a learning environment that is more personal, effective, and relevant to the spiritual and intellectual needs of the digital generation. This article aims to analyze the Multiple Intelligences (MI) method in the development of Islamic learning methodology, in the era of digital transformation. This article maps the relevance of the MI approach to the needs of contemporary Islamic education. The results of the study indicate that MI can be an effective pedagogical approach, as long as it is reconstructed through an Islamic value framework.